Endothelial Basement Membrane Components and Their Products, Matrikines: Active Drivers of Pulmonary Hypertension? - Mutgan, Ayse Ceren (Cells, 2020)
Pulmonary arterial hypertension (PAH) is a vascular disease that is characterized by elevated pulmonary arterial pressure (PAP) due to progressive vascular remodeling. Extracellular matrix (ECM) deposition in pulmonary arteries (PA) is one of the key features of vascular remodeling. Emerging evidence indicates that the basement membrane (BM), a specialized cluster of ECM proteins underlying the endothelium, may be actively involved in the progression of vascular remodeling. The BM and its steady turnover are pivotal for maintaining appropriate vascular functions. However, the pathologically elevated turnover of BM components leads to an increased release of biologically active short fragments, which are called matrikines. Both BM components and their matrikines can interfere with pivotal biological processes, such as survival, proliferation, adhesion, and migration and thus may actively contribute to endothelial dysfunction. Therefore, in this review, we summarize the emerging role of the BM and its matrikines on the vascular endothelium and further discuss its implications on lung vascular remodeling in pulmonary hypertension.